2015
DOI: 10.4103/0970-9185.155151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between dexmedetomidine and fentanyl on intubation conditions during awake fiberoptic bronchoscopy: A randomized double-blind prospective study

Abstract: Background and Aims:Various drugs are used for providing favorable intubation conditions during awake fiberoptic intubation (AFOI). However, most of them cause respiratory depression and airway obstruction leading to hypoxemia. The aim of this study was to compare intubation conditions, and incidence of desaturation between dexmedetomidine and fentanyl group during AFOI.Material and Methods:This randomized double-blind prospective study was conducted on a total of 60 patients scheduled for elective laparotomie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 25 publications
(26 reference statements)
8
49
2
Order By: Relevance
“…In concordance with our study, Mondal et al . [ 17 ] also observed similar changes in hemodynamics in their study. They observed that patients of dexmedetomidine group showed better hemodynamic stability.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In concordance with our study, Mondal et al . [ 17 ] also observed similar changes in hemodynamics in their study. They observed that patients of dexmedetomidine group showed better hemodynamic stability.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast with our study, Mondal et al . [ 17 ] observed higher sedation scores (3 ± 0.371) with dexmedetomidine group than fentanyl group (2.07 ± 0.254). ( P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Another study used dexmedetomidine for awake fibre-optic bronchoscopy and did not find bradycardia, which can be explained by the use of glycopyrrolate prior to starting dexmedetomidine infusion, as done in our study also. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Glycopyrrolate has also been used as an antisialogogic in previous study before the bronchoscopy. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Monitored anesthesia care has been widely used in many clinical fields such as gastrointestinal endoscopy, septoplasty, thyroplasty, interventional or radiological procedures, cataract surgery, and awake bronchoscopy intubation (Bekker and Sturaitis, 2005; Busick et al, 2008; Goksu et al, 2008; Dogan et al, 2010; Parikh et al, 2013; Mondal et al, 2015). It can provide suitable intraoperative conditions for both patients and surgeons alike while avoiding the adverse reactions of GA, e.g., hemodynamic instability and prolonged emergence.…”
Section: Discussionmentioning
confidence: 99%